A The Role of the Interprofessional Team in Managing Cardiovascular Emergencies in Primary Healthcare Facilities: The Role of the Interprofessional Team in Managing Cardiovascular Emergencies in Primary Healthcare Facilities - Evianta, Mars (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Cardiovascular emergencies require immediate and appropriate treatment. The presence of healthcare personnel has long been an issue in hospitals, despite the abundance of medical and paramedical professionals. These medical and paramedical personnel generally possess basic life-saving skills. The Code Blue team can be activated by initiating the code blue system. Code blue is a system that activates an emergency response for patients experiencing cardiac arrest, respiratory arrest, or other critical situations requiring resuscitation. This study aims to examine the role of the interprofessional team and code blue in managing cardiac and respiratory arrest in hospitals. The research employs a narrative review method. The role of the code blue team is crucial in managing cardiac and respiratory arrest in hospitals. This study shows that, in general, all cases of cardiac and respiratory arrest emergencies require the activation of the code blue team to receive immediate care and assistance. The presence of the code blue team helps reduce mortality rates and increases the likelihood of patients experiencing Return of Spontaneous Circulation (ROSC).